LANGUAGE, IDENTITY, AND SOCIAL FRAGMENTATION IN THE POST-TRUTH ERA: A LITERATURE REVIEW OF DIGITAL CITIZENSHIP EDUCATION: BAHASA, IDENTITAS, DAN FRAGMENTASI SOSIAL DI ERA POST-TRUTH: KAJIAN LITERATUR TERHADAP PENDIDIKAN KEWARGANEGARAAN DIGITAL - Yeri Utami; Atikah Ulayya; Usep Saepul Ahyar; Yunanto Andang Trihantoro; Oman Sukmana (SOSIOEDUKASI, 2025)
This research departs from the post-truth phenomenon which is characterized by the dominance of subjective opinions and emotions in shaping public perception, which has a serious impact on social cohesion in the digital space. Language plays an important role in this process, not only as a means of communication, but also as a discourse that reproduces power and social identity. This research aims to analyze how digital language shapes and fragments social identities, as well as to evaluate the role of digital citizenship education in facing the challenges of disinformation and social polarization. The approach of this research is qualitative with a systematic literature review method based on a critical sociological perspective. Data is obtained from journal articles, academic books, educational policies, and other literature sources collected through a targeted search in scientific databases. The analysis is carried out thematically and interpretively with an emphasis on concepts from Foucault, Hall, Bauman, Giroux, and Habermas. The results of the study show that the digital space creates a new form of social fragmentation, but also opens up opportunities for intervention through critical education. Therefore, digital citizenship education needs to be systematically integrated to form inclusive, critical, and ethical citizens in communicating in the digital era.